IMPLEMENTASI USERMANAGER SEBAGAI RADIUS SERVER PADA ROUTER BOARD MIKROTIK RB750GR3 - Zulkarnaen Zulkarnaen (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2021)
In today’s digital era, The need for data communication services is increasing along with the development of increasingly rapid communication technology, indirectly changing the paradigm that currently distance cannot prevent people from interacting both directly and virtually. Various operating system configuration options on network devices are carried out in an effort to provide stable network access services. Mikrotik can be integrated into a home internet network or a small to large scale network. This research is focused on being able to maximize the functions of the MikroTik operating system by integrating the user manager as an authentication system and server radius, making it easier for network administrators to manage users who are connected to the network either through wired media or wireless or wifi networks. This study uses a routerboard mikrotik rb750gr3 that functions as a hotspot server as well as a radius server that is integrated with the usermanager, the results of the tests carried out, the use of the mikrotik RB750GR3 which is integrated with the usermanager package on the network (NandaHotspot) runs well, The application of usermanager as a radius server can increase network security and the process of creating or generating user hotspots can be done quickly so that it is very helpful for network providers in managing and monitoring all users connected to their network